Two new combinations in Polygonaceae for the Flora of Taiwan - Hsu, Tian-Chuan; Chung, Shih-Wen (Phytotaxa, 2016)
When preparing the Illustrated Flora of Taiwan, we noticed that new combinations are necessary for two endemic species in family Polygonaceae Jussieu (1789: 82), Polygonum pilushanense Y.C.Liu & C.H.Ou in Ou (1976: 123) and P. yatagaianum Mori (1937: 25), to fit recently revised taxonomic framework (Sanchez et al. 2009, 2011, Schuster et al. 2011, 2015). Brief notes on their taxonomic positions are also provided.